1973
DOI: 10.1017/s002185960005886x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tiller age and time of nitrogen stress on seed production of Paspalum plicatulum

Abstract: Paspalum plicatulum was grown at Brisbane in boxes of sand receiving basal nutrients and frequent irrigation; weekly levels of ammonium nitrate application were varied according to growth and development stage.The rate of tiller appearance increased to a maximum 40-50 days after sowing and almost ceased thereafter. Tiller leaf number, survival, fertility, inflorescence branching, seeds per raceme and seed size were positively related to tiller age. Young tillers were more sensitive to variations in nitrogen su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Sward age has a strong effect on Paspalum SY, and greater seed production has been observed in the first year of production. Previous research on P. plicatulum (Chadhokar & Humphreys, 1973) and P. notatum (Rios et al., 2020) showed most of the response variables, except seed weight, exhibited significantly better performance during the first year of production. Therefore, productive behavior over time requires more research.…”
Section: Discussionmentioning
confidence: 82%
“…Sward age has a strong effect on Paspalum SY, and greater seed production has been observed in the first year of production. Previous research on P. plicatulum (Chadhokar & Humphreys, 1973) and P. notatum (Rios et al., 2020) showed most of the response variables, except seed weight, exhibited significantly better performance during the first year of production. Therefore, productive behavior over time requires more research.…”
Section: Discussionmentioning
confidence: 82%
“…In Exp. 3 (1969 and1970), herbage was cut back in all treatments on the same base date (Ti). In Exp.…”
Section: Resultsmentioning
confidence: 99%
“…There was no evi dence that late N increased 1000-grain weight. In Paspalum plicatulum, Chadhokar and Humphreys (1970) observed that seed production was independent of N nutrition after head emergence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to climatic conditions, sward age has been reported as a factor with a strong effect on Paspalum seed yield. Chadhokar and Humphreys (1973) reported that Paspalum plicatulum Michx. produced a higher seed set during the first year of seed production.…”
Section: Discussionmentioning
confidence: 99%